Complex Feline Disease Mapping Using a Dense Genotyping Array - Hernandez, Isabel; Hayward, Jessica J.; Brockman, Jeff A.; White, Michelle E.; Mouttham, Lara; Wilcox, Elizabeth A.; Garrison, Susan; Castelhano, Marta G.; Loftus, John P.; Gomes, Filipe Espinheira; Balkman, Cheryl; Brooks, Marjory B.; et al. (Frontiers in Veterinary Science, 2022)
The current feline genotyping array of 63 k single nucleotide polymorphisms has proven its utility for mapping within breeds, and its use has led to the identification of variants associated with Mendelian traits in purebred cats. However, compared to single gene disorders, association studies of complex diseases, especially with the inclusion of random bred cats with relatively low linkage disequilibrium, require a denser genotyping array and an increased sample size to provide statistically significant associations. Here, we undertook a multi-breed study of 1,122 cats, most of which were admitted and phenotyped for nine common complex feline diseases at the Cornell University Hospital for Animals. Using a proprietary 340 k single nucleotide polymorphism mapping array, we identified significant genome-wide associations with hyperthyroidism, diabetes mellitus, and eosinophilic keratoconjunctivitis. These results provide genomic locations for variant discovery and candidate gene screening for these important complex feline diseases, which are relevant not only to feline health, but also to the development of disease models for comparative studies.